Fill the Earth and Subdue It: Christian Nationalism, Ethno‐Religious Threat, and Nationalist Pronatalism. Issue 4 (7th September 2022) - Perry, Samuel L.; McElroy, Elizabeth E.; Schnabel, Landon; Grubbs, Joshua B.
Abstract : What fuels both enthusiasm for increasing "American" birth rates and fears about their decline? Citing the prevalence of fertility campaigns in authoritarian regimes characterized by ethno‐nationalist Christianity, we theorize that, in addition to patriarchal attitudes, perceived ethno‐cultural threat and desire for ethno‐cultural dominance substantially drive "nationalist pronatalism" (promoting fertility to strengthen "the nation" and avoid national decline). We expect pronatalist ideology focused on American births is associated with (1) belief that dominant cultural group members (Whites, Christians, men) are threatened and (2) White Christian nationalism—an ideology that looks to conform American identity and values to those of a traditionalist, ethnicized Christianity. Recent, nationally representative data reveal Christian nationalist ideology is the second strongest predictor of support for nationalist pronatalism, second only behind patriarchal attitudes. This association is stronger for men and virtually non‐existent among Blacks. The belief that Whites or Christians face "the most discrimination" as opposed to various minorities also predicts nationalist pronatalism. Contemporary support for pronatalist ideology focused on American births is thus undergirded not only by attitudes that subordinate women but also (1) an ethno‐racially contingent ideology that insists the United States should reflect and institutionalize traditionalist Christian culture and (2) perceptions that Christians and Whites are persecuted.